2015
DOI: 10.4236/psych.2015.68099
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Brazilian Homeless Compared with Non-Psychiatric and Psychiatric Patients

Abstract: Personality disorders are regarded as conditions that involve a maladaptive personality functioning. Homelessness is a worldly debated phenomenon. The present study aimed to understand the situation of homelessness related to the health sector, instead of considering it only as a social or economic problem. Research was conducted with three different groups, male and female, living in a Metropolitan area of Southeast Brazil, the first composed of 71 homeless people; the second, 74 psychiatric patients; and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A study conducted in Brazil with the use of the Personality Disorders Dimensional Inventory showed that homeless people display antisocial, schizoid, and dependent PDs more often than others. However, in a non-clinical student group, borderline and obsessive-compulsive personality patterns of disorders were found to be frequent (Bartholomeu et al, 2015). The sample in this study was not, however, large and not randomized, which makes it difficult to compare these results with other studies.…”
Section: South Americamentioning
confidence: 71%
“…A study conducted in Brazil with the use of the Personality Disorders Dimensional Inventory showed that homeless people display antisocial, schizoid, and dependent PDs more often than others. However, in a non-clinical student group, borderline and obsessive-compulsive personality patterns of disorders were found to be frequent (Bartholomeu et al, 2015). The sample in this study was not, however, large and not randomized, which makes it difficult to compare these results with other studies.…”
Section: South Americamentioning
confidence: 71%